Penerapan Metode Qira’ah dalam Pembelajaran Bahasa Arab bagi Siswa MA Walisongo Sukajadi Lampung Tengah - Latifah, Umi; Azizah, Nurul; Nikmah, Mamluatun (Al Maghazi : Arabic Language in Higher Education, 2023)
This research was to find out the Qira'ah method that used in Arabic learning and to find out the obstacles in using it’s method. The researchers used a qualitative approach. The qualitative approach was a research approach that was oriented to natural phenomena. Because of this orientation, it was naturalistic and basic or natural and cannot be done in a laboratory but must be done on the spot. The results of the research on the application of the Qira'ah method explain that learning Arabic at MA Wali Songo Sukajadi Central Lampung must combine other methods, such as the Tarjamah grammar method, the auditory speech method or the direct method. Thus, inhibiting factors such as students' lack of knowledge about Hijaiyah letters, lack of interest in learning Arabic, and students' weak ability to master mufrada must be combined with the application of the Qira'ah method with other methods. And about the teacher's efforts to improve students' Arabic classes through additional study, pay special attention to it and need to emphasize memorization of students' vocabulary. Keywords: Application Qira'ah Method, Learning Arabic, Learning Qira'ah Method